Institutional alternatives in African smallholder irrigation: lessons from international experience with irrigation management transfer - Shah, Tushaar; van Koppen, Barbara; Merrey, Douglas J.; Lange, M. de; Samad, M. (International Water Management Institute, 2002)
This report reviews several decades of global experience in transferring management of government-run irrigation systems to farmer associations or other nongovernmental agencies in an attempt to apply the lessons of success to the African smallholder irrigation context.